Analysis of the Effectiveness of Financial Technology (Fintech) in Simplifying Credit Access for MSMEs in Urban Areas - Muhammad Rizal; Idhar Idhar; Wahyu Prasetyo; Abdullah Abdullah (Economica Insight, 2026)
The development of Financial Technology (fintech) has brought significant changes to the financial system, particularly in providing credit access for Micro, Small, and Medium Enterprises (MSMEs) in urban areas. This study aims to analyze the effectiveness of fintech in simplifying MSME credit access in 2025, viewed from aspects of accessibility, speed of fund disbursement, financial inclusion, and its impact on business performance. The research method used is a qualitative-descriptive approach with literature study and secondary data analysis from financial institution reports, relevant authorities, and previous research findings. The results indicate that fintech, particularly peer-to-peer lending and digital financing platforms, has proven effective in expanding MSME credit access in urban areas through faster processes, simpler requirements, and the utilization of digital technology. However, challenges such as credit risk, financial literacy, and consumer protection remain major concerns. Therefore, synergy among the government, fintech providers, and MSME actors is required to maximize the sustainable benefits of fintech.